2020
DOI: 10.1155/2020/8183420
|View full text |Cite
|
Sign up to set email alerts
|

Weighed Gene Coexpression Network Analysis Screens the Potential Long Noncoding RNAs and Genes Associated with Progression of Coronary Artery Disease

Abstract: Background. Coronary artery disease (CAD) is a type of heart disease with a high morbidity rate. This study is aimed at identifying potential biomarkers closely related to the progression of CAD. Materials and Methods. A microarray dataset of GSE59867 was downloaded from a public database, Gene Expression Omnibus, which included 46 cases of stable CAD without a history of myocardial infarction (MI), 30 cases of MI without heart failure (HF), and 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Network inference. Although differential expression analysis is a rather routine approach to obtain a list of biomarker candidates for understanding molecular disease processes, analyses involving molecular networks facilitate identification of more robust biomarkers and causal mechanisms [ 75 , 99 , 100 , 101 , 102 , 103 ]. By reverse-engineering disease-specific regulatory networks or pathways, for instance in a multi-omics setting, it is possible to trace the effects of a disease-associated genetic variant throughout the cell [ 104 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Network inference. Although differential expression analysis is a rather routine approach to obtain a list of biomarker candidates for understanding molecular disease processes, analyses involving molecular networks facilitate identification of more robust biomarkers and causal mechanisms [ 75 , 99 , 100 , 101 , 102 , 103 ]. By reverse-engineering disease-specific regulatory networks or pathways, for instance in a multi-omics setting, it is possible to trace the effects of a disease-associated genetic variant throughout the cell [ 104 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study investigated gene expression microarray data from CAD patients without a history of MI, patients with MI but without heart failure, and patients with MI and heart failure (46, 34, and 30 cases, respectively) [ 102 ]. After detecting differentially expressed genes and long-non-coding RNAs (lncRNAs) between the three groups, the authors applied GO and KEGG pathway enrichment analysis to annotate the identified genes with their biological context.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang et al reported that tetrahydrobiopterin reverses left ventricular hypertrophy and diastolic dysfunction in spontaneously hypertensive rats through PI3K/Akt. 22 It has been reported that the MAPK signalling pathway is involved in coronary artery disease 23 and that adriamycin induces HF via the MAPK/AMPK pathway. 24 Moreover, cardiac contractility modulation has been shown to alleviate chronic HF in a rabbit model through the PI3K/ AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…4) Molecular biology studies have shown that several genes like long noncoding RNA (lncRNA) and messenger RNA (mRNA) are related to the occurrence and development of CAD. 5,6) mRNA is generally considered to be regulated by microRNA (miRNA), which is commonly used in studying various diseases (including CAD). In addition, lncRNA was more stable than mRNA.…”
mentioning
confidence: 99%